Globalisation and Inclusive Growth in Sub Saharan Africa: The Role of Institutional Quality (2023)
This study examines the relationship between globalisation and inclusive growth by considering the modulating role of institutional quality. To achieve our broad objective, we use data from 45 African economies over 1996–2018 to deter mine the panel cointegration and cointegrating regression association between inclusive growth, globalisation and institutional quality. To determine a suitable estimation technique for the empirical analysis, several pre-estimation tests were conducted. After confirming the existence of cointegration and slope hetero geneity, we adapted the long-run panel cointegrating methods—the fully modified ordinary least squares and dynamic ordinary least squares estimations. The results from both show that aggregate globalisation and its various dimensions have positive and significant effects on inclusive growth. Besides the direct positive impact on inclusive growth, globalisation has indirect positive and significant impact on inclusive growth through institutional quality. Finally, some policy implications are highlighted.